ON THE DERIVATION OF COMPOUND WORDS - Aliyeva Shakhnoza Aibekovna (Western European Studies, 2023)
This article expresses opinions about word formations produced by the affixation method, their analysis and principles. Some theoretical ideas about the basal and derived structure are also given. Complex compound suffixes in derived words are studied in the derivational aspect.
Keywords: derivation operator; operand; basal structure